Geoeconomics of Chip War: TSMC’S Influence in Tech Titans Rivalry - Zulkarnain, Muhammad Fitrah; Al-Fadhat, Faris; Sitompul, Eiga (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2026)
This research analyzes the geoeconomic aspects of the global semiconductor industry, concentrating on China's strategic goal of semiconductor self-sufficiency and Taiwan's reliance on Taiwan Semiconductor Manufacturing Company (TSMC). The research used a qualitative cross-case analysis of secondary data, such as policy papers, government reports, and industry analyses, to compare China's state-driven semiconductor development strategy with Taiwan's economic leverage through TSMC. By highlighting how semiconductors function as strategic economic assets that influence global power dynamics, this study fills a gap in the literature that frequently views semiconductor rivalry as merely a technological or security concern. The results exhibit that Taiwan's ability to produce the most advanced chips strengthens its relationship with the US but also makes it more vulnerable to global risks. China's investments, like the